Transfusion-related Acute Lung Injury in the Critically Ill: Prospective Nested Case-Control Study - Gajic, Ognjen; Rana, Rimki; Winters, Jeffrey L; Yilmaz, Murat; Mendez, Jose L; Rickman, Otis B; O'Byrne, Megan M; Evenson, Laura K; Malinchoc, Michael; DeGoey, Steven R; Afessa, Bekele; Hubmayr, Rolf D; et al. (American journal of respiratory and critical care medicine, 2007)
Acute lung injury (ALI) that develops 6 hours after transfusion (TRALI) is the leading cause of transfusion-related mortality. Several transfusion characteristics have been postulated as risk factors for TRALI, but the evidence is limited to retrospective studies. To compare patient and transfusion risk factors between patients who do and do not develop ALI. In this prospective cohort study, consecutive transfused critically ill patients were closely observed for development of ALI. Donor samples were collected from the transfusion bags. Risk factors were compared between patients who developed ALI after transfusion and transfused control patients, matched by age, sex, and admission diagnosis. Seventy-four of 901 transfused patients developed ALI within 6 hours of transfusion (8%). Compared with transfused control subjects, patients with ALI were more likely to have sepsis (37 vs. 22%, P = 0.016) and a history of chronic alcohol abuse (37 vs. 18%, P = 0.006). When adjusted for patient characteristics, transfusion of plasma from female donors (odds ratio [OR], 5.09; 95% confidence interval [95% CI], 1.37-18.85) rather than male donors (OR, 1.60; 95% CI, 0.76 to 3.37), number of pregnancies among the donors (OR, 1.19; 95% CI, 1.05 to 1.34), number of donor units positive for anti-granulocyte antibodies (OR, 4.85; 95% CI, 1.32-17.86) and anti-HLA class II antibodies (OR, 3.08; 95% CI, 1.15-8.25), and concentration of lysophosphatidylcholine in the donor product (OR, 1.69; 95% CI, 1.10 to 2.59) were associated with the development of ALI. Both patient and transfusion risk factors determine the probability of ALI after transfusion. Transfusion factors represent attractive targets for the prevention of ALI.